Antenatal myomectomy: when to intervene and why? - Jaiswar, Shyam P.; Mehrotra, Seema; Sankhwar, Pushpa L.; Verma, Manju L.; Gupta, Shruti; Aggarwal, Sneha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Uterine myomas affect 2-10% of pregnant women. In every one out of ten patients, myomas complicate the course leading to adverse pregnancy outcomes such as placental abruption, premature rupture of membranes, placenta previa, preterm labor, fetal malpresentation, Myomectomy is rarely performed during pregnancy because of fear of miscarriage and the risk of uncontrolled hemorrhage. Surgical management is needed in selected cases where conservative management fails to manage symptoms and there is a substantial risk of adverse pregnancy outcomes. This article provides insight into the safety, risks and benefits of antenatal myomectomy. This is a retrospective analysis of 6 patients who underwent myomectomy between 16-19 weeks of gestation at our tertiary care centre. Decision for surgical management was based on large fibroid size and refractory pain. Myoma was enucleated via transverse incision and reconstruction of uterine wall was done in double layer. None of the patients in our study had miscarriage, preterm labour, premature rupture of membranes, placental abruption. All patients delivered at term with median gestational age of 37 weeks, 5 by elective caesarean section and one patient delivered vaginally after induction of labour. None of the patients delivered a growth-restricted fetus or a fetus with a congenital anomaly. No adverse maternal or fetal outcome was reported. Antenatal myomectomy should not be done as a routine procedure. However, in carefully selected patients in skilled hands it is a safe procedure and gives good pregnancy outcomes while avoiding the complications typically linked to the presence of myomas.